Modern Problems of Attracting Students to the National Cultural Heritage - Boykuzieva R'no Karimovna (Zien Journals, 2023)
The article reveals the social significance, pedagogical nature and features of national cultural and intangible values in Uzbekistan during the period of independence
Keywords: Higher dynamic strategies; creative and creative competences; cultural heritage